Garage Sale as an Opportunity for Entrepreneurial Students in The Fashion Field - Mala Maulidina Pratiwi; Muhammad Giatman; Yuliana (Enrichment : Journal of Management, 2022)
The purpose of this study is to determine the garage sale business strategy for students in the fashion sector that can be used as a business opportunity, in addition to knowing how the garage sale business strategy is for students, and what factors support students in choosing to run a garage sale business. . This study uses a qualitative descriptive approach to describe a garage sale business as an entrepreneurial opportunity for students with data collection techniques in the form of interviews and observations. Data analysis used triangulation, namely checking the validity of the data by checking data from the same source with different techniques and using the Guttman scale to analyze the supporting factors. The results show that garage sale data can be used as an entrepreneurial opportunity because it has several advantages, students' strategies in running a garage sale business through SWOT analysis and a garage sale business feasibility study, as well as several factors that support students to make a garage sale selling entrepreneurial opportunities. namely internal factors which include intelligence, motivation, ideals, talents, attitudes, personality, and creativity. for external factors include role factors, activities, competitors, capital and opportunities.